European Resuscitation Council Guidelines 2021: Education for resuscitation - Greif, Robert; Lockey, Andrew; Breckwoldt, Jan; Carmona, Francesc; Conaghan, Patricia; Kuzovlev, Artem; Pflanzl-Knizacek, Lucas; Sari, Ferenc; Shammet, Salma; Scapigliati, Andrea; Turner, Nigel; Yeung, Joyce; et al. (Resuscitation, 2021)
These European Resuscitation Council education guidelines, are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. This section provides guidance to citizens and healthcare professionals with regard to teaching and learning the knowledge, skills and attitudes of resuscitation with the ultimate aim of improving patient survival after cardiac arrest.